Energy-Efficient Mobility Prediction Routing Protocol for Freely Floating Underwater Acoustic Sensor Networks - Alqahtani, Ghida Jubran; Bouabdallah, Fatma (Frontiers in Communications and Networks, 2021)
Recently, there has been an increasing interest in monitoring and exploring the Underwater environments for scientific applications such as oceanographic data collection, marine surveillance, and pollution detection. Underwater Acoustic Sensor Networks (UASN) have been proposed as the enabling technology to observe, map and explore the ocean. Due to the unique characteristics of Underwater aquatic environments which are: low bandwidth, long propagation delays, and high energy consumption which makes the data forwarding process very difficult. Moreover, the mobility of the underwater sensors is considered as an additional constraint for the success of the data forwarding process. That being said, most of the data forwarding protocols do not realistically consider the dynamic topology of the Underwater environment as sensor nodes move with the water currents which is a natural phenomenon. In this research, we propose a Mobility Prediction Optimal Data Forwarding (MPODF) Protocol for Underwater Acoustic Sensor networks based on mobility prediction. Indeed, by considering a realistic, physically inspired mobility model, our protocol succeeds to forward every generated data packet through one single best path without the need to exchange notification messages, thanks to a mobility prediction module. Simulation results show that our protocol achieves a high packet delivery ratio, high energy efficiency, and reduced end-to-end delay.